Empowering Students’ Social Attitudes in EFL Classroom through Teacher Talk - Almas Rizkika Nabila (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The purpose of this study is to reveal the role of teacher in the form of teacher talk to empower students’ social attitudes in EFL classroom interaction as well as the difficulties that teacher faced. Through the qualitative method, this study describes the way English teacher in conveying the teacher talk during EFL interaction. The result showed that teacher used the features of teacher talk in the form of (1) praises and encouragement, (2) accepting students’ ideas, (3) asking question, (5) giving information, (6) giving direction and (7) criticizing students’ behavior. Moreover, teacher talk also empower students’ social attitude of honest, disciplined, responsible, caring, responsive and proactive. Teacher talk also represents the power for controlling students, the power to give the corrective action and the power in providing the supportive action for students. Lastly, this study also described some difficulties faced by teachers in delivering the teacher talk as well as the suggestion for future research. Keywords: Critical Discourse Analysis, Power, Social Attitudes, Teacher Talk